2010
DOI: 10.1111/j.1398-9995.2010.02467.x
|View full text |Cite
|
Sign up to set email alerts
|

Does allergic rhinitis exist in infancy? Findings from the PARIS birth cohort

Abstract: These results support the hypothesis that AR could begin as early as 18 months of life. Suspicion of AR should be reinforced in infants with parental history of AR or biological evidence of atopy, particularly blood eosinophilia and sensitization to inhalant allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 37 publications
1
44
1
1
Order By: Relevance
“…Unlike the prevalence of atopic dermatitis, the prevalence of allergic rhinitis-like symptoms did not differ among phenotypes, probably because this disorder is a challenge to diagnosis in infants. 39 Risk factors associated with the identified phenotypes Differences in patterns of risk for each phenotype helped us to solve 2 challenges to clustering methods. 40 First, these differences supported the validity of the classification, and second, they made it possible to formulate hypotheses about the cause of phenotypes.…”
Section: Respiratory and Allergic Phenotypesmentioning
confidence: 99%
“…Unlike the prevalence of atopic dermatitis, the prevalence of allergic rhinitis-like symptoms did not differ among phenotypes, probably because this disorder is a challenge to diagnosis in infants. 39 Risk factors associated with the identified phenotypes Differences in patterns of risk for each phenotype helped us to solve 2 challenges to clustering methods. 40 First, these differences supported the validity of the classification, and second, they made it possible to formulate hypotheses about the cause of phenotypes.…”
Section: Respiratory and Allergic Phenotypesmentioning
confidence: 99%
“…This question assumes that the respondent can correctly identify a cold or 'flu', for example, some children may only have significant symptoms with a combination of both allergic inflammation and a coexisting viral infection. This is a particularly issue in the preschool age (18). Furthermore, ISAAC uses the presence of coexisting itchy eyes to identify allergic rhinitis although this is probably more relevant for pollen-induced rather than rhinitis driven by perennial allergens such as house dust mite.…”
Section: Prevalence and Epidemiologymentioning
confidence: 99%
“…In a report from the pollution and asthma risk: an Infant Study (PARIS), 9.1% of the 1859 toddlers in the study cohort reported allergic rhinitis-like symptoms at age 18 months. 5 Though symptoms can develop at younger age in our study we included only children above the age of six years. In this group there were more boys than girls with M: F ratio of 3:2.…”
Section: Discussionmentioning
confidence: 99%